A communicative approach to foreign language learning and computers - Fontal Reglero, Rosa (Huarte de San Juan. Filología y Didáctica de la Lengua, 1997)
Innovation in educational technology and, more specifically applied to foreign language teaching and learning, has revealed an increasing market of software learning materials (CD-ROM platform) that, is gradually drawing a new perspective on methodological issues and on the different components involved in the learning process. On one hand, there is the issue of how these new materials comply with the communicative approach, considered to be the general norm in the field, and on the other, how they influence the changing roles of the teacher and the learner as well as the whole learning process.